The effectiveness of using red betel leaf (piper ornatum) infusion compared to binahong leaf (anredera cordifolia) infusion in healing external genital infections - Manaf, Salmiani Abdul; Novemi, Novemi (Institute of Computer Science (IOCS), 2024)
The group of women vulnerable to viral and bacterial infections. Efforts to prevent more serious external genitalia infections often involve daily genital hygiene habits. One of the efforts made is utilizing plants as traditional remedies, such as using boiled water from red betel leaves and Binahong leaves to cleanse external genitalia. This study aims to analyze the effectiveness of using boiled water from red betel leaves (Piper Ornatum) compared to Binahong leaf decoction (Anredera cordifolia) on the healing level of infected external genital organs in female cockle seekers. The method used is a quasi-experimental study with randomization and pre-post test design. The population consists of 134 female cockle seekers, with 30 individuals in treatment group I and 30 individuals in treatment group II, based on predefined inclusion criteria. Data analysis was performed using the Wilcoxon signed-rank test and Mann-Whitney test. The results show a significant difference in the healing of external genital infections in female cockle seekers before and after the use of boiled water from red betel leaves, with p=0.000 (p<0.05), as well as a significant difference before and after the use of Binahong leaf decoction, with p=0.000 (p<0.05). The findings indicate that boiled water from red betel leaves is more effective in healing external genital infections compared to Binahong leaf decoction among female cockle seekers in Krueng Tibang, with an average infection healing score of 25.